KOMUNIKASI KELUARGA SINGLE MOTHER DALAM PENGASUHAN ANAK DI PEKANBARU - Kiki Syarafina; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research is motivated by the author's interest in the rise of the Single mother phenomenon in Pekanbaru. Whether it's a woman who becomes a single mother due to divorce, the death of her partner, or is no longer supported or abandoned by her partner, a single mother still has the obligation to meet the needs of her family as a father and mother at the same time. Single mothers must be able to balance their time to earn a living as the head of the family and still provide love as a mother. Single mothers will face various kinds of challenges and trials in raising their children alone. Therefore, this study aims to determine the meaning, communication experience and self-concept of single mothers in child care in Pekanbaru This study used a qualitative research method using a phenomenological approach and consisted of 5 informants selected using purposive techniques. Data and information were collected through in-depth interviews, observation and documentation. Data analysis techniques are data reduction, data modeling and conclusion drawing/verification. To carry out data validity, the authors use the technique of extending observations, increasing persistence, and increasing reference materials The results showed that the meaning of single mother in child care in Pekanbaru consisted of being receptive to single mother status which included a sincere attitude in living life, starting a new life, and being ready to risk becoming a single mother. Furthermore, a pleasant communication experience for single mothers is getting understanding from children, being proud to be an independent woman, and getting support from family and the surrounding environment. And unpleasant communication experiences, namely getting unfavorable treatment from the surrounding environment, difficulty raising children alone, and economic problems. Then the single mother self-concept in child care consists of a positive self-concept and a negative self-concept. Positive self-concept consists of single mother acceptance of single mother status in child care, self-disclosure to the environment and people around, good treatment from the surrounding environment, and openness to experience. While the negative self-concept of single mothers in child care in Pekanbaru consists of unfavorable treatment from the surrounding environment, tends to close themselves to experience, and closes themselves to new experiences and people.